Pendekatan Gestalt Untuk Mengatasi Kecenderungan Narsistik Pada Mahasiswa Melalui Layanan Konseling Kelompok - Dhea Aulia Putri; Yenti Arsini; Nidaul Ummah (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2024)
The attitude of loving oneself too much and having to be admired excessively is a condition that is considered a form of narcissistic attitude, tending to those who are too excessive in loving and admiring themselves often become a laughing stock for their social environment, because theydisplay different patterns of behavior, too much. in appreciating themselves, those in the narcissistic category need praise and recognition in their lives, especially when using social media one of them they want to get good comments praising themselves and want to get lots of likes for what they post. This study aims to overcome excessive attitudes such as narcissism with a gestalt approach, one of which is the practice technique I am responsible for, the exercise technique I am responsible for can effectively help overcome narcissistic attitudes experienced by students, they are taught to be able to change their attitude responsibly and admit that they can overcome their narcissistic attitudes, so that narcissistic attitudes that sometimes like to ignoretheir environment can be changed by individuals who are affected by narcissism. With the research method of literature study based on articles that support and are in accordance with the narcissistic variable and the gestalt approach. The results of the study prove that narcissistic behavior can be overcome by using the gestalt approach, namely the practice technique I am responsible for with group counseling setting, namely group counselling.